RECONSTRUCTION OF CRIMINAL PROCEDURAL LAW (KUHAP) ABOUT THE DETENTION BASED ON JUSTICE - Muhammad Khambali; Teguh Prasetyo; Sri Endah Wahyuningsih (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Detention is a form of deprivation of freedom of movement a person. In the custody of a conflict between two principles, namely the right to move someone who is a human right that must be respected on the one hand, and the interests of public order on the other side of which must be preserved for the people or the people of evil deeds suspect or defendant. Therefore, the detention should be performed if necessary at all. Defects in detention can lead to things fatal to many parties, including anchoring.1 The provisions on the validity (rechwaardigheid) detention stated in Article 21 paragraph (4) Criminal Procedure Code, while the need to (noodzakelijkheid) detention stated in Article 21 paragraph (1) Criminal Code. Therefore, the competent authorities did or did not make an arrest (Article 20 of the Code of Criminal Procedure), the transfer of the type of detention (Article 22 of the Criminal Procedure Code), and the suspension of detention (Article 31 of the Criminal Code) against the suspect or defendant are at an institution or institutions, it provides opportunities for officials authorities detain, switching types of detention, detention suspend deviates by detaining suspects or defendants arbitrarily or even exceeds authority. Containment actions can also be used as a commodity "buy-sell" by detaining a suspect or defendant then "trade" to suspend the detention or transfer of the type of detention for the "price" certain. Researchers do research on the regulatory limit of detention, including the detention and transfer of the type of suspension of detention of suspects or accused general crime. Researchers interested in conducting research on detention, including the transfer of the type of detention and the suspension of the arrest of the suspect or defendant, which further analyze the passage and find construction rules detention of suspects or defendants in the Criminal Code.